VIRULENCE OF RICE BROWN PLANTHOPPER, Nilaparvata lugens (Stsl) POPULATION FROM KHAMMAM DISTRICT OF TELANGANA STATE AGAINST RICE GENOTYPES AND ITS MORPHOMETRICS - B. RAJESWARI; C. SRINIVAS, SUBHASHREE PRIYADARSHINI, V. JHANSI LAKSHMI, M. SHESHU MADHAV (The Journal of Research, PJTSAU, 2021)
Thirty two rice genotypes with known and unknown genetics were evaluated for their resistance reaction to rice brown planthopper (BPH) Nilaparvata lugens (Stål) population collected from Khammam district of Telangana state, India by Standard seedbox Screening method at ICAR-Indian Institute of Rice Research, Rajendranagar, Hyderabad during 2018-19. Four genotypes viz., PTB 33 (Bph2, Bph3 and Bph32 genes), RP 2068-18-3-5 (Bph33t + gene), RP Bio 4918-230S (bph39 and bph40 genes) and IR 62 (Bph3 gene) were found resistant with a damage score of 1.1-3.0. Two genotypes viz., MTU 1010 and Sinnasivappu with unknown genetics were moderately resistant. The other genotypes were susceptible to Khammam BPH population. The resistant genotypes can be used in the breeding programme to develop brown planthopper resistant varieties for that region. The morphometrics i.e total body length and width, abdominal length and width, length of rostrum, length of tibial spur, antennal length, interocular distance of five nymphal instars (1st, 2nd, 3rd, 4th and 5th), winged (macropterous), wingless (brachypterous) females and males were recorded. In case of macropterous and brachypterous adults the length and width of wing were also measured. The females measured from 2.6 mm to 3.2 mm and the males measured from 1.9 to 2.3 mm in length. The length of tibial spur was 0.29 to 0.35 mm and that of rostrum was 0.86 mm in males and 1.19 mm in females. The nymphal instars increased in body length from 1.19 mm (1st instar) to 3.3 mm (5th instar).